Sustainable land management learning from the past for the future - Kapur, Selim; Eswaran, Hari.; Blum, Winfried E.H.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
Soil quality is threatened by many human-induced activities, but can also be improved by good land management. In the relatively short history of mankind on earth, the landscape and soils of the world have been drastically modified from their natural state. Landscapes altered by man's activities are termed Anthroscapes which are inextricably linked to culture and history. The challenges for today's scientists are to devise and implement sustainable land management strategies in order to preserve the land for the benefit of future generations. This book is a valuable compendium of the research experiences so far gained in studies of the context and concept of the Anthroscape and highlights the potential future contributions of such research to sustainable development.
Electronic reproduction.
Keywords: Natural resources -- Management; Sustainable agriculture; Electronic books